International Perspectives on Inclusive Education In the Light of Educational Justice - Rusli, Nor Amalina (Central European Journal of Educational Research, 2024)
Bibliography of the reviewed book: Norwich, B., Seitz, S., Mackenzie, A., Magnússon, G., & Barow, T. (2024). International perspectives on inclusive education: In the light of educational justice. European Journal of Special Needs Education, 39(2), 327–336. https://doi.org/10.1080/08856257.2023.2299148